2013
DOI: 10.1111/tsq.12029
|View full text |Cite
|
Sign up to set email alerts
|

Trust, Culture, and Cooperation: A Social Dilemma Analysis of Pro-Environmental Behaviors

Abstract: Social dilemmas require a choice between cooperation, or sacrificing for the greater good, and self-interest. One commonly studied social dilemma is environmental conservation. Previous work suggests that trust predicts cooperation in the form of environmental protection. We contend that this view ignores cultural factors. Building on prior cross-cultural research, we predict an interaction between strength of social ties and trust on cooperation. Findings from General Social Survey data indicate that low trus… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
37
1
3

Year Published

2014
2014
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 48 publications
(43 citation statements)
references
References 64 publications
2
37
1
3
Order By: Relevance
“…Northern Regions are apparently more efficient in door to door collection, but the difference could also depend on higher levels of trust (Irwin and Berigan, 2013), and of social capital (Tsai, 2008) e and specifically on more effective social norms. A stronger sense of citizenship may provide a possible explanation in this regard.…”
Section: Geographical Area Conceptual Definitions and Data Sourcesmentioning
confidence: 98%
“…Northern Regions are apparently more efficient in door to door collection, but the difference could also depend on higher levels of trust (Irwin and Berigan, 2013), and of social capital (Tsai, 2008) e and specifically on more effective social norms. A stronger sense of citizenship may provide a possible explanation in this regard.…”
Section: Geographical Area Conceptual Definitions and Data Sourcesmentioning
confidence: 98%
“…Some of these include education, income, and ideology. Research on social dilemmas involving environmental public goods has identified trust as a key variable predicting the willingness to cooperate toward collective goals ( Van Lange, Van Vugt, Meertens, and Ruiter 1998;Liebe, Preisendörfer, and Meyerhoff 2011;Irwin and Berigan 2013). The research presented here seeks to connect these two areas of research by exploring an individual's willingness to sacrifice for the environment as contingent upon the interaction of education, income, and ideology with free rider fears.…”
Section: Jeremiah Bohrmentioning
confidence: 96%
“…For example, surveys suggest that individuals who are trusting are more likely to recycle (81), use public transportation (91), buy green products (29), and join an environmental organization (80), although effect sizes vary across cultures (34), and the reverse hypothesis-that environmentally minded individuals are more trusting-cannot be ruled out. Studies showing that unequal societies invest less in pro-environmental policies, monitoring, and research (39,55,85,93) also suggest that inequality undermines the willingness to cooperate to protect the environment.…”
Section: Social Cohesion and Cooperationmentioning
confidence: 99%